Designing News Text Teaching Materials with Higher-Order Thinking Skills based on Website - Bagas Romadhoni Sugiarto; Cahyo Hasanudin; Sutrimah (IKIP PGRI Bojonegoro, 2026)
News text learning in junior high school is still dominated by the use of printed teaching materials which tend to be monotonous. This research aims to develop teaching materials for HOTS-based news texts in class VII news text learning at the junior high school level. The research uses the Research and Development (R&D) method with the ADDIE model which includes the stages of analysis, design, development, implementation, and evaluation. The subjects of the study were grade VII students in three schools in Bojonegoro district. Data was collected through student needs questionnaires, expert validation sheets, and news text writing tests. The results of the study showed that the teaching materials obtained a feasibility percentage of 90.00% from material experts and 93.34% from media experts with the very feasible category. The average student score increased from 40.90 in the pretest to 81.52 in the post. The results of the N-Gain calculation obtained a score of 0.68257 with the medium category. Thus, the teaching materials for HOTS-based news texts are feasible and effective for improving student learning outcomes.